Evaluasi Kinerja Kompor UB-03-1 Berbahan Bakar Limbah Industri Kayu Olahan, Tempurung Kelapa, Pelepah Sawit, Dan Ranting Kayu Akasia - Eko Karmiza; Sri Helianty; Zulfansyah Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The availability of biomass as a source of primary energy in Indonesia is very abundant, reaching 280 million barrels of oil equivalent (BOE) and approximately 84% of the biomass has been used for the household sector. The application of gasification stove especially in cooking purposes can increase the efficiency of fuel usage. This research used UB-03-1 semi-gasification with various of biomass, such as acacia of branches, palm frond, tropical wood and coconut shell. The moisture content measurement of biomass fuels was determined using oven-dry method. The efficiency of the biomass fuels in UB-03-1 stove between 13,18 – 45,91%. Tropical wood had the highest energy efficiency of 45,91% and coconut shell had the lowhest energy efficiency of 13,18%. UB-03-1 stove works in the range of 3,5 to 11,5 kWth of fire power. The research obtained indicate that a variety of biomass fuels in Riau can perform well in UB-03-1 stove, such as acacia branches having 4,2 kWth fire power, palm frond having 4,86 kWth fire power, tropical wood having 11,5 kWth fire power and coconut shell having 3,5 kWth fire power, thus the need for adoption to combat crisis energy household sector problem Keywords : biomass, semi-gasification stove, water boiling test, UB-03-1